TUJUAN BERIBADAH KEPADA TUHAN BERDASARKAN MAZMUR 63:2-5 DAN IBRANI 10:25 - Trisno Kurniadi (Manna Rafflesia, 2015)
The term worship is no stranger to believers. But now there are many shifts to the motivation and purpose of worship. Worship aimed at worshiping the Triune God has now been diverted for the purposes of human emotionality. The psalmist and writer of the Hebrews stressed the importance of understanding the purpose of worship. In this article we will discuss "the purpose of worship" according to Psalm 63: 2-5 and Hebrews 10:25. It is hoped that through this article believers can understand the purpose of worshiping the Triune God.